Strategic assessment of banana research priorities - Pemsl, Diemuth E.; Staver, Charles (CGIAR Research Program on Roots, Tubers and Bananas, 2014)
In 2013/14 RTB conducted a strategic assessment of research priorities for its major target crops (cassava, banana, potato, sweet potato, and yam). All five studies followed a common framework jointly developed by a priority assessment taskforce. The six-step process for the assessment comprised of i) definition of agro-ecological zones and mapping of crop production to identify target are as; ii) analysis of key constraints; iii) selection of research options to be included in the assessment; iv) quantification of model parameters; v) estimation of research impacts; and vi) communication of findings. This report gives an overview of the approach and then focuses on the methods and results for the assessment of banana research priorities (steps 3 through 5). Based on the results of a large scale, carefully targeted online banana expert survey (523 respondents from more than 50 countries) and the outcomes of a global expert workshop held in early 2013, 12 high priority candidate banana research options were identified. Based on availability of time and resources, the following six banana research options were included in the quantitative assessment: 1) recovery of production affected by banana bunchy top virus BBTV); 2) integrated management of banana Xanthomonas wilt (BXW) and other bacterial diseases: develop improved cultural practices & low-cost diagnostic kits; 3) integrated management of banana Xanthomonas wilt (BXW) and other bacterial diseases: resistant genetically modified (GM) East African Highland banana (EAHB) varieties; 4) sustainable intensification of banana-based cropping systems; 5) breeding EAHB varieties resistant to nematodes, weevils, and black leaf streak; 6) breeding plantain varieties resistant to black leaf streak, nematodes, weevils, and with improved quality traits.